2010
DOI: 10.1016/j.pnpbp.2010.04.023
|View full text |Cite
|
Sign up to set email alerts
|

The BDNF Val66Met polymorphism is an independent risk factor for high lethality in suicide attempts of depressed patients

Abstract: Some authors have reported an association of BDNF Val66Met polymorphism with suicidal behavior and/or clinical aspects of suicidal attempts. We evaluated, here, the impact of BDNF Val66Met polymorphism on the clinical characteristics of suicide attempts. The study was conducted on a cohort of 120 consecutive patients who were admitted to the Emergency Hospital of Porto Alegre, Brazil, due to a suicide attempt. Variables of univariate analyses were included in a logistic regression model to test whether the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 39 publications
3
35
1
1
Order By: Relevance
“…BDNF 196A was shown to be a risk factor for suicide in some studies conducted among psychiatric populations [11,12,13,14,15]. In our study, we found a protective effect of the BDNF 196A-carrying genotypes on attempted suicide in the elderly population.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…BDNF 196A was shown to be a risk factor for suicide in some studies conducted among psychiatric populations [11,12,13,14,15]. In our study, we found a protective effect of the BDNF 196A-carrying genotypes on attempted suicide in the elderly population.…”
Section: Discussionsupporting
confidence: 73%
“…However, their results do not agree. Five studies [11,12,13,14,15] found that the 196A allele was a risk factor for suicidal behavior, while a further 2 studies [16,17] suggested that the 196G allele was the primary risk factor for attempted suicide. On the other hand, other studies [9,18,19,20] did not support the association of the BDNF G196A polymorphism and suicidal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Frequency of the Met/Met genotype has also been associated with attempted suicide among schizophrenia probands. 215 Of concern, the 66Met allele has been linked to lethality among depressed patients who attempt suicide 216 and the utilization of violent suicide methods among female carriers of a 66Met allele. 217 Adding credence for a role of BDNF in SB, a recent meta-analysis reported that the 66Met allele was significantly associated with history of suicide attempt, 218 while another reported that the 66Met allele was associated with attempted but not completed suicide.…”
Section: Schizophrenia and Psychosismentioning
confidence: 99%
“…One recent report failed to find an association between BDNF polymorphisms and SB, but found associations of SNPs in NTRK2 gene (encoding TrkB) with suicide attempt in 394 depressed patients, replicated in another population (Kohli et al, 2010). Another study showed that the BDNF Val66Met polymorphism might be associated with lethality in suicide attempts (Schenkel et al, 2010). From the previously mentioned findings, the BDNF-dependent pathway may play an important role in the SB pathogenesis.…”
Section: Dopaminergic Systemmentioning
confidence: 98%